Determinants of Underweight Among Children Aged 6-23 Months in Central Sulawesi Province (SSGI Analysis 2022) - Arini, Firlia Ayu; Azahra, Nabilla Zalfa; Sufyan, Dian Luthfiana (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Underweight in children, defined as failure to achieve a normal weight for age, poses a significant risk of stunting if not properly addressed. This study investigates the determinants of underweight among children aged 6–23 months in Central Sulawesi Province through quantitative analysis of secondary data from the 2022 SSGI. The research employed a cross-sectional design with a sample size of 1,991 children, analyzing the data through chi-square tests and logistic regression. Multivariate analysis identified several significant factors: low birth weight (low birth weight (LBW)) (p=0.000; OR 2.304; 95% CI 1.620–3.277), exclusive breastfeeding (p=0.023; OR 1.507; 95% CI 1.057–2.149), frequency of complementary feeding (CF) (p=0.043; OR 0.775; 95% CI 0.606–0.992), age at introduction of CF (p=0.043; OR 0.708; 95% CI 0.507–0.989), acute respiratory infections (ARI) (p=0.005; OR 1.429; 95% CI 1.117–1.828), and diarrhea (p=0.045; OR 1.368; 95% CI 1,007–1,859). The study concludes that low birth weight (low birth weight (LBW)) is the primary risk factor for underweight in this population. Recommendations include further research into the quantity and diversity of complementary foods, the frequency of CF, and maternal health factors during pregnancy.